Effects of Pollution on Ecosystems, Living Beings, and the Environment - Suwanaruang , Theeranat (Effects of Pollution on Ecosystems, Living Beings, and the Environment, 2023)
The author's book, The Effect of Pollution, Soil, Water, and Air on Life: Effects on the Use of Soil, Water, and Air on Life, Ecosystem, and Environment, aims to inform readers about environmental issues land way Impacts on water, air, and people the business, the environment, and the ecosystem may all profit from this student Researchers, academics, citizens, and interested authors hope that readers will be motivated by this book to learn more about life and living contentedly. Limit and avoid toxins Pollution that could be harmful to people Environment, soil, water, air, and all living things.